To the wonderful rivers of Pittsburgh, Op.193 : for winds and percussion orchestra in antiphonal manner (1997)
Firmada, datada y paginada. -- Formato: Wood choir: 1 Piccolo, 2 Flutes (1st with alto flute in G), 2 Oboes, 1 English horn, 2 Clarinets in Bb, 1 Bass clarinet in Bb, 1 Contrabass clarinet in Eb, 2 Bassoons, 1 Contrabassoon; Brass choir: 4 horns in F, 3 trumpets in Bb, 3 trombones (3rd is bass), 1 Tuba; Percussion 1: Timpani (4), Temple bells (5); Percussion 2: Tubular bells I (chimes), Snare drum, Xylophone; Percussion 3: Tubular bells II (chimes), Temple blocks (3), Marimba; Percussion 4: Tubular bells III (chimes), Cymbals, Bongos (2); Percussion 5: Vibraphone I, Bass drum, Maracas (2); Percussion 6: Vibraphone II, Large tam-tam, Roto tom (3), Whip; 1 Celesta, 1 Harp. -- Obra comisionada: commissioned by the American Waterways Wind Orchestra, Music director Bobert Austin Boudreau, for the 40th Season, 1997. -- El documento contiene gráfico de la posición de la orquesta en el escenario y explicación de convenciones en la partitura. -- Fotocopia anillada del documento (32 hojas), 43 x 28 cm. -- Se localizan 2 agujeros en el lateral izquierdo en todas las hojas, manchas de humedad, pedazos de cinta adhesiva, manchas de corrector y anotaciones a mano del compositor. -- El compositor posee dos fechas de nacimiento registradas en diferentes obras. Está en revisión documental. 1933 o 1943.